Clinical Prospect of Mesenchymal Stromal/Stem Cell-Derived Extracellular Vesicles in Kidney Disease: Challenges and the Way Forward - Maja Kosanović; Bojana Milutinović; Tanja J. Kutzner; Yanis Mouloud; Milica Bozic (Pharmaceutics, 2023)
Kidney disease is a growing public health problem worldwide, including both acute and chronic forms. Existing therapies for kidney disease target various pathogenic mechanisms; however, these therapies only slow down the progression of the disease rather than offering a cure. One of the potential and emerging approaches for the treatment of kidney disease is mesenchymal stromal/stem cell (MSC) therapy, shown to have beneficial effects in preclinical studies. In addition, extracellular vesicles (EVs) released by MSCs became a potent cell-free therapy option in various preclinical models of kidney disease due to their regenerative, anti-inflammatory, and immunomodulatory properties. However, there are scarce clinical data available regarding the use of MSC-EVs in kidney pathologies. This review article provides an outline of the renoprotective effects of MSC-EVs in different preclinical models of kidney disease. It offers a comprehensive analysis of possible mechanisms of action of MSC-EVs with an emphasis on kidney disease. Finally, on the journey toward the implementation of MSC-EVs into clinical practice, we highlight the need to establish standardized methods for the characterization of an EV-based product and investigate the adequate dosing, safety, and efficacy of MSC-EVs application, as well as the development of suitable potency assays.